PENGARUH PENAMBANGAN EMAS TRADISIONAL TERHADAP STATUS HARA LAHAN HUTAN PRIMER BOJONG PARI, SUKABUMI - juhaeti, Titi; Naiola, B.P. (BERITA BIOLOGI, 1997)
Studies on the soil nutrient status of a degraded forest under traditional gold mining have been conducted in a forest area in Bojong Pari,Sukabumi,West Java by analyzing nutrient content of soil taken from degraded forest and also from the adjacent virgin forest as a control. Meanwhile, litter deposits from forest floor were collected to be compared. The result showed that the soil is belongs to clay type with the acidity ranged between (based on H2O 1:2,5) 4,72-4,83.Soil macro nutrient content from degraded forest showed N 0,041%; P 0,059 mg/100 g and K 0,222 ppm, this value are lower than that from virgin forest. The litter deposits ( dry weight) taken from degraded forest are 110,53 g/m lower than the virgin forest (230,42 gAn ).It means that traditional gold mining has changed the nutrient status of the Bojong Pan Forest area.